A Preclinical Systematic Review of the Effects of Chronic Exercise on Autophagy-Related Proteins in Aging Skeletal Muscle - Wang, Cenyi; Liang, Jiling; Ren, Yuanyuan; Huang, Jielun; Jin, Baoming; Wang, Guodong; Chen, Ning (Frontiers in Physiology, 2022)
Background: Exercise is one of the most effective interventions for preventing and treating skeletal muscle aging. Exercise-induced autophagy is widely acknowledged to regulate skeletal muscle mass and delay skeletal muscle aging. However, the mechanisms underlying of the effect of different exercises on autophagy in aging skeletal muscle remain unclear. Methods: A systematic review was performed following an electronic search of SCOPUS, PubMed, Web of Science, ScienceDirect, and Google Scholar and two Chinese electronic databases, CNKI and Wan Fang. All articles published in English and Chinese between January 2010 and January 2022 that quantified autophagy-related proteins in aging skeletal muscle models. Results: The primary outcome was autophagy assessment, indicated by changes in the levels of any autophagy-associated proteins. A total of fifteen studies were included in the final review. Chronic exercise modes mainly comprise aerobic exercise and resistance exercise, and the intervention types include treadmill training, voluntary wheel running, and ladder training. LC3, Atg5-Atg7/9/12, mTOR, Beclin1, Bcl-2, p62, PGC-1α, and other protein levels were quantified, and the results showed that long-term aerobic exercise and resistance exercise could increase the expression of autophagy-related proteins in aging skeletal muscle (p < 0.05). However, there was no significant difference in short term or high-intensity chronic exercise, and different types and intensities of exercise yielded different levels of significance for autophagy-related protein expression. Conclusion: Existing evidence reveals that high-intensity exercise may induce excessive autophagy, while low-intensity exercise for a short period (Intervention duration <12 weeks, frequency <3 times/week) may not reach the threshold for exercise-induced autophagy. Precise control of the exercise dose is essential in the long term to maximize the benefits of exercise. Further investigation is warranted to explore the relationship between chronic exercise and different exercise duration and types to substantiate the delaying of skeletal muscle aging by exercise.